Evaluation of microbiological risks in cream as a raw material for buttermaking - G. M. Sviridenko; M. B. Zakharova; N. V. Ivanova (Пищевые системы, 2022)
The article presents the research results of studying the influence of various groups of microorganisms — coliform bacteria, lactic acid microorganisms, yeast, and spore bacteria — on the quality and storage capacity of cream used as a raw material for buttermaking. The objects of study were the following: cream as a raw material before and after pasteurization, as well as pasteurized cream seeded with testing cultures of various types of spoilage microorganisms. The samples were stored at temperature conditions of 30 ± 1 °C, 10 ± 1 °C, and 4 ± 2 °C. To evaluate the quality and storage capacity of cream used as a raw material, its microbiological and physicochemical indicators were determined by standardized methods: bacterial number, titratable acidity, indicators of oxidative spoilage of the fat phase. Organoleptic characteristics were evaluated in terms of taste, consistency and appearance. Research results have shown that the greatest microbiological risks during storage of cream used as a raw material are associated with lactococci, coliform bacteria and yeast. Microbiological risks caused by seeding of cream with thermophilic streptococcus, spore bacteria of the genus Bacillus and spore anaerobic microorganisms of the genus Clostridium are less significant, which is associated with the lack of development and metabolism of these groups of microorganisms at storage temperatures of 10 ± 1 °C and 4 ± 2 °C. At the same time, the reason for the rejection of cream contaminated with these testing cultures, at a storage temperature of 4 ± 2 °C, is primarily a decrease in organoleptic indicators, and at a temperature of 10 ± 1 °C — an excess in bacterial number.